Mixed bacterial culture mediated direct conversion of bio-glycerol to diols - Parate, Roopa; Mane, Rasika; Dharne, Mahesh; Rode, Chandrashekhar (Bioresource Technology, 2018)
Direct and economic transformation of biodiesel derived crude glycerol is gaining more significance. During screening of bacterial cultures Klebsiella pneumoniae and Enterobacter aerogenes were able to convert crude bio-glycerol to 2,3-butanediol (2,3-BDO) and 1,3-propanediol (1,3-PDO), as major compounds, ethanol and acetoin as minor compounds, with a conversion of 69% and 79% respectively. Process optimization could achieve maximum conversion at pH 7.0, 37 degrees C, 30-40 g/L glycerol and 1.5 g of inoculum until 120 h. Mixed cultures led to complete glycerol conversion with optimal yield and productivity. An innovative approach of using crude glycerol for sustained growth and tolerance of bacteria as source of carbon and energy makes this study more significant. In addition to this, a mixed culture concept introduced here is expected to make impact in process economics for industrial scale synthesis for direct transformation of glycerol into C3 and specifically, C4 diols.
Keywords: 1; 2; 3-Butanediol; 3-Propanediol; Bioconversion; Bioglycerol; Mixed culture

Biodegradation of mixed polycyclic aromatic hydrocarbons by pure and mixed cultures of biosurfactant producing thermophilic and thermo-tolerant bacteria - Mehetre, Gajanan T.; Dastager, Syed G.; Dharne, Mahesh S. (Science of the Total Environment, 2019)
Applicability of thermophilic and thereto-tolerant microorganisms for biodegradation of polycyclic aromatic hydrocarbons (PAHs) with low water solubility is an interesting strategy for improving the biodegradation efficiency. In this study, we evaluated utility of thermophilic and thermo-tolerant bacteria isolated from Unkeshwar hot spring (India) for biodegradation of four different PAHs. Water samples were enriched in mineral salt medium (MSM) containing a mixture of four PAHs compounds (anthracene: ANT, fluorene: FLU, phenanthrenc: PHE and pyrene: PYR) at 37 degrees C and 50 degrees C. After growth based screening, four potent strains obtained which were identified as Aeribacillus pallidus (UCPS2), Bacillus axarquiensis (UCPD1), Bacillus siamensis (GHP76) and Bacillus subtilis subsp. inaquosorum (U277) based on the 16S rRNA gene sequence analysis. Degradation of mixed PAH compounds was evaluated by pure as well as mixed cultures under shake flask conditions using MSM supplemented with 200 mg/L concentration of PAHs (50 mg/L of each compound) for 15 days at 37 degrees C and 50 degrees C. A relatively higher degradation of ANT (92% - 96%), FLU (83% - 86%), PHE (16% - 54%) and PYR (51% - 71%) was achieved at 50 degrees C by Aeribacillus sp. (UCPS2) and mixed culture. Furthermore, crude oil was used as a substrate to study the degradation of same PAHs using these organisms which also revealed with similar results with the higher degradation at 50 degrees C. Interestingly, PAH-degrading strains were also positive for biosurfactant production. Biosurfactants were identified as the variants of surfactins (lipopeptide biosurfactants) based on analytical tools and phylogenetic analysis of the surfactin genes. Overall, this study has shown that hot spring microbes may have a potential for PAHs degradation and also biosurfactant production at a higher temperature, which could provide a novel perspective for removal of PAHs residues from oil contaminated sites. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Biodegradation; Biosurfactants; Crude oil; Mixed culture; PAHs; Thermophiles